Determinación de la capacidad de inducción de callo de dos variedades de frijol Phaseolus vulgaris L. en dos medios de cultivo (ING) - Madriz Muñoz., Jorge (1996)
The cotiledon, epicotyl and leaf callogenesis capacity was studied on the bean commercial varieties Huasteco and Huetar cultivated on Fj and PC-L2 media. The three explant types from the cultivar Huasteco formed callus on both tested media. The Huetar explants formed callus only on the PC-L2 medium; however, the cotiledon explant formed callus on Fj medium. The highest accumulated relative growth index was observed at the end of the first and second week. One week later (end of third week), this parameter varied among explants, cultivars and culture media, showing a decreasing tendency at the fourth week.